The generalist Inga subnuda subsp. luschnathiana (Fabaceae): negative effect of floral visitors on reproductive success?. (27th January 2015) - Avila, R.; Pinheiro, M.; Sazima, M.; Dafni, A.
Abstract Inga species are characterised by generalist or mixed pollination system. However, this feature does not enhance reproductive rates in species with very low fruit set under natural conditions. Some ecological and genetic factors are associated with this feature, and to test the effect of massive visits on pollination success in Inga subnuda subsp. luschnathiana, we studied the efficacy of polyads deposited on stigmas of flowers isolated from visitors and polyads exposed to visitors. The proportion of polyads fixed in stigmas decreased after exposure to visitors (24 h) in comparison to stigmas isolated from visitors (hummingbirds, bees, wasps, hawkmoths and bats), and fruit set was very low. Furthermore, nectar production, sugar composition and other floral biology traits were evaluated. Increased nectar production, sugar availability and sucrose dominance during the night indicates adaptation to nocturnal visitors and supports their role as main pollinators; although the brush‐flower morphology, time of anthesis, nectar dynamics and chemical composition also allow daytime visitors. Thus the species is an important resource for a diverse group of floral visitors. We conclude that excess visits (diurnal and nocturnal) are responsible for the decrease in fixed polyads in stigmas of I. subnuda subsp. luschnathiana flowers, thus contributing, with others factors, to its low fruit set. Therefore, the generalist pollination system does not result in reproductive advantages because the low fruit set in natural conditions could be the result of a negative effect of visitors/pollinators.